Analysis of student errors in solving grade 2 number problems based on Kastolan theory at MIN 1 Banyuwangi - Lebriansari, Santi (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2025)
While everyone makes mistakes, only the wise are able to learn from them. The purpose of this study was to examine the errors students make when attempting to complete non-routine tasks. Kastolan's theory, which encompasses conceptual, procedural, and technological errors, served as the basis for the error analysis. Students from a prestigious public school in Banyuwangi, Indonesia, located on the eastern tip of Java, participated in this qualitative study. The selected participants were 26 students from class 2A. Data were collected through a written test given to students. The test consisted of five essay questions that had to be answered in two 30-minute sessions. The results were then evaluated. The findings showed conceptual, procedural, and technical errors. This study revealed that conceptual mastery was the main error found in students' answers. Further studies are expected to reduce numerical errors among students.